In vitro plant regeneration system for tropical butternut squash genotypes (Cucurbita moschata) - Valdez-Melara, Marta (2009)
An efficient and reproducible method for regeneration of commercial and pure lines of tropical butternut squash (Cucurbita moschata) plants via somatic embryogenesis was developed. The influence of genotype, explant source, N6-benzylaminopurine (BAP), 2,4-dichlorophenoxyacetic acid (2,4-D) and 2,4,5-trichlorophenoxyacetic acid (2,4,5-T) concentration on somatic embryogenesis induction was investigated. Friable embryogenic calli was produced from zigotic embryos (53-56%) and cotyledons from seedlings (70%) of C. moschata cv. Sello de Oro cultured on callus induction medium (CIM) supplemented with 0.5 mg/l or 3.5 mg/l 2,4-D. No embryogenic calli was obtained from leaf segments of C. moschata cv. Sello de Oro cultured on CIM supplemented with different concentrations of BAP and 2,4-D and cotyledons from seedlings of C. moschata cv. PVG 04 cultured on CIM with BAP and 2,4,5-T. Embryogenic calli induction was achieved in 75% C. moschata pure lines evaluated and calli percentage frequency range from 5% to 34%. Successful acclimatization of squash in vitro plants was achieved in the greenhouse and in the field. Regenerated plants appeared morphologically normal and set flowers and fruits with seeds that could germinate normally.